Classification of Liver Patient Dataset Using Machine Learning Algorithms - Muthuselvan, S; Rajapraksh, S; Somasundaram, K; Karthik, K (International Journal of Engineering and Technology, 2018)
Prediction of the disease in the human being is the very long and difficult process in early days. Now a days, computer aided diagnosis is the important role in the medical industry for predicting, analyzing and storing medical information with the images. In this paper will discuss and classify the liver patients with the help of the liver patient dataset with the help of the machine learning algorithms. WEKA is the software used here for implement the some of the classification algorithms with the data selected from the liver disease dataset. After the successful implementation of the all the algorithms, the best algorithms selected from the output of the all the algorithms execution.Â